Staging Lung Cancer: Current Controversies and Strategies - Riyad Karmy-Jones; Robert H Hyland; Joseph W Lewis; Paul Kvale (Canadian Respiratory Journal)
A consistent approach to staging is required for the rational management of lung cancer. This paper was prepared at the request of the Standards Committee of the Canadian Thoracic Society, and reviews and discusses the relative merits of the available methods of staging. Whichever methods are chosen by a particular institution, the following points must be stressed. No patient can be considered automatically "unresectable" when chest radiography and/ or computed tomography demonstrate adenopathy or only suggest local invasion. Clinical and/or radiographical evidence suggesting extensive local or metastatic disease should be evaluated as completely as possible before subjecting the patient to a possible "nontherapeutic" thoracotomy. Finally, in some cases thoracotomy is required to decide whether the lesion is "completely" resectable.